Analisis Yuridis Sistem Pelayanan BPJS Kesehatan dalam Meningkatkan Kepercayaan Peserta BPJS: Studi Kasus Di BPJS Kesehatan Surakarta - Vita Setya Permatahati; Aris Prio Agus Santoso; Rezi Rezi (Lembaga Pengembangan Kinerja Dosen, 2023)
The Social Security Administrative Body is a legal entity in administering social security programs to ensure that all people are able to meet the basic needs of a decent life. The purpose of this research is to analyze the BPJS Kesehatan service system which is capable of anticipating a surge in patients seeking treatment abroad. This study uses a Statute Approach and a conceptual approach using the interview method. Data analysis used qualitative analysis techniques to test the validity of the data in this study by looking for existing reference sources. Based on the results of the research, it shows that the National Social Security System (SJSN) is organized with a Social Insurance mechanism in which each participant is required to pay contributions to provide protection for socio-economic risks that befall participants and/or their family members. The BPJS service arrangement or system is complete by providing basic services and referrals as long as the person is still alive but not for treatment abroad. In the absence of this regulation, it automatically prevents someone from seeking treatment abroad, so they continue to seek treatment at home. The BPJS Kesehatan office in serving patients seeking treatment abroad has not found BPJS patients consulting for treatment abroad.